2008
DOI: 10.1186/1471-2164-9-348
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering downstream gene targets of PI3K/mTOR/p70S6K pathway in breast cancer

Abstract: Background: The 70 kDa ribosomal protein S6 kinase (RPS6KB1), located at 17q23, is amplified and overexpressed in 10-30% of primary breast cancers and breast cancer cell lines. p70S6K is a serine/threonine kinase regulated by PI3K/mTOR pathway, which plays a crucial role in control of cell cycle, growth and survival. Our aim was to determine p70S6K and PI3K/mTOR/p70S6K pathway dependent gene expression profiles by microarrays using five breast cancer cell lines with predefined gene copy number and gene express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(53 citation statements)
references
References 41 publications
5
48
0
Order By: Relevance
“…On the other hand, subtype A had significant downregulation of the activating thr-412 phosphorylation on p70S6K, the exact opposite effect seen in the subtype B (Table 6). That cases in both subtypes are highly correlated with the disease suggests that p70S6K dysregulation may have less to do with the pathogenesis of the disease and perhaps more to do with the different correlation structure observed between the two subtypes since p70S6K plays an important role in regulating both translation and transcription (12).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, subtype A had significant downregulation of the activating thr-412 phosphorylation on p70S6K, the exact opposite effect seen in the subtype B (Table 6). That cases in both subtypes are highly correlated with the disease suggests that p70S6K dysregulation may have less to do with the pathogenesis of the disease and perhaps more to do with the different correlation structure observed between the two subtypes since p70S6K plays an important role in regulating both translation and transcription (12).…”
Section: Discussionmentioning
confidence: 99%
“…Heinonen et al [13] have reported that p70S6K is over-expressed in primary breast cancer tissues, and its upregulation is associated with aggressive disease and poor prognosis of patients with breast cancer. Moreover, p70S6K also has a crucial role in cell growth by regulating cell size and progression of cell cycle [14]. However, the roles of mTOR/p70S6K signal transduction pathway in osteosarcoma, which is one of the most rapidly growing sarcomas, remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Heinonen et al has determined p70S6K and PI3K/mTOR/p70S6K pathway dependent gene expression profiles by micro-arrays using five breast cancer cell lines with predefined gene copy number and gene expression alterations. He suggested that p70S6K over-expression is associated with aggressive disease and poor prognosis of breast cancer patients; the potential downstream targets of p70S6K and the whole PI3K/mTOR/p70S6K pathway identified, may have diagnostic value [56].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 99%